Honolulu [videorecording (DVD)] - Fields, Herbert, 1897-1958; Partos, Frank, 1901-1956; Cummings, Jack, 1900-1989; Buzzell, Edward, 1895-1985; Powell, Eleanor, 1912-1982; Young, Robert, 1907-1998; Burns, George, 1896-1996; Allen, Gracie, 1902-1964 (Archive collection., 2011)
Handsome movie heartthrob Brooks Mason is tired of being besieged by adoring fans. When he meets his exact double, a shy Hawaiian plantation owner named George Smith, they decide to switch for a month. Mason sails to Hawaii, falls in love with a beautiful dancer. Smith is sent to a New York hospital, thanks to overzealous fans.